Informality, frictions, and macroprudential policy - Ben Hassine, Moez,Rebei, Nooman (International Monetary Fund, 2019)
We analyze the effects of macroprudential policies through the lens of an estimated dynamic stochastic general equilibrium (DSGE) model tailored to developing markets. In particular, we explicitly introduce informality in the labor and goods markets within a small open economy embedding financial frictions, nominal and real rigidities, labor search and matching, and an explicit banking sector. We use the estimated version of the model to run welfare analysis under optimized monetary and macroprudential rules. Results show that although informality reduces the efficiency of macroprudential policies following a convex fashion, combining the latter with an inflation targeting objective could be beneficial
10.5089/9781498320856.001
Keywords: Graue Literatur; Banks and Banking; Financial Markets and the Macroeconomy; Labor Demand; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Macroeconomics: Consumption; Saving; Wealth; Economic Development: Urban; Rural; Regional; and Transportation Analysis; Infrastructure; Labor Economics: General; Macroeconomics; Labour; income economics; Macroprudential policy; Self-employment; Banking; Consumption; Housing; Financial sector policy and analysis; Labor; National accounts; Economic policy; Self-employed; Banks and banking; Consumption; Economics; Saving and investment; Labor economics; Macroprudential Policies; Monetary Policy; Collateral Constraints; Informal Sector; Developing Market